2013
DOI: 10.1161/strokeaha.111.000434
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Flow Diverter (Surpass) for Unruptured Intracranial Aneurysms

Abstract: Background and Purpose— In patients harboring intracranial aneurysms, the major goal in treatment is to prevent bleeding. A new generation of an endoluminal device (Surpass Flow Diverter [Surpass]) was developed to reconstruct parent artery and occlude the aneurysm. We present our clinical and angiographic single-center experience. Methods— Patients with a wide range of complex unruptured aneurysms were treated with the Surpass placed in the parent arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
130
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 41 publications
0
130
0
1
Order By: Relevance
“…Similarly, the recently introduced Surpass flow diverter (Stryker Neurovascular) was also designed with different structures: The 2.5-mm-diameter device has 48 wires, whereas the 3-and 4-mm devices have 72 wires and the 5-mm device is constructed of 96 wires. 11 Moreover, their users experienced neither the complications of device migration nor incomplete neck coverage due to device shortening as reported in early series. 10,12 We believe that these structural improvements combined with extensive operator expertise (both of our operators had practiced the delivery and deployment of the Tubridge on models and gained full knowledge of the Tubridge characteristics before placing it in humans) reduced the chance of technical adverse events in patients treated with FD.…”
Section: Characteristics and Feasibility Of Tubridge Flow Divertersmentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, the recently introduced Surpass flow diverter (Stryker Neurovascular) was also designed with different structures: The 2.5-mm-diameter device has 48 wires, whereas the 3-and 4-mm devices have 72 wires and the 5-mm device is constructed of 96 wires. 11 Moreover, their users experienced neither the complications of device migration nor incomplete neck coverage due to device shortening as reported in early series. 10,12 We believe that these structural improvements combined with extensive operator expertise (both of our operators had practiced the delivery and deployment of the Tubridge on models and gained full knowledge of the Tubridge characteristics before placing it in humans) reduced the chance of technical adverse events in patients treated with FD.…”
Section: Characteristics and Feasibility Of Tubridge Flow Divertersmentioning
confidence: 86%
“…5,29,30 However, studies with a long-term follow-up and larger series are necessary. De Vries et al 11 recently reported their 6-month follow-up result, which showed a complete occlusion (94%), including 1 case with a 95%-100% occlusion. However, their research contained a high number of small aneurysms, which may influence the occlusion rate.…”
Section: Efficacy Of Tubridge Flow Diverter Implantationmentioning
confidence: 95%
See 1 more Smart Citation
“…For aneurysm treatment, flow diverters were deployed using previously described techniques [12][13][14] after meticulous measurement of the parent artery size at the proximal and distal segments of the aneurysm. These measurements were made on DSA images and 3D images reconstructed from rotational angiograms on workstations of biplane angiography units (Artis zee; Siemens, Erlangen, Germany).…”
Section: General Description Of the Endovascular Proceduresmentioning
confidence: 99%
“…Clinical studies report that the aneurysm is never closed by a thrombus at end-of-procedure angiographythat is, after 1 or 2 hours, 23,24 while at 6-month follow-up angiography, complete occlusion was found in 68%-94% of patients. 23,[25][26][27][28][29][30][31] Although it is difficult to judge when the thrombus formation begins in patients, we suppose that the process is strongly accelerated in the in vitro setup, which potentially influences clotting mechanisms. Dosed anticoagulation by means of Clexane aimed to allow the in vitro use of blood for several hours and does not depict the clinical standard of antiplatelet therapy with aspirin and clopidogrel.…”
Section: Limitationsmentioning
confidence: 99%